2019
DOI: 10.1051/0004-6361/201834818
|View full text |Cite
|
Sign up to set email alerts
|

Mass discrepancy analysis for a select sample of Type II-Plateau supernovae

Abstract: The detailed study of supernovae (SNe) and their progenitors allows a better understanding of the evolution of massive stars and how these end their lives. Despite its importance, the range of physical parameters for the most common type of explosion, the type II supernovae (SNe II), is still unknown. In particular, previous studies of type II-Plateau supernovae (SNe II-P) showed a discrepancy between the progenitor masses inferred from hydrodynamic models and those determined from the analysis of direct detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
0
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 92 publications
(120 reference statements)
5
40
0
14
Order By: Relevance
“…This is consistent with the red supergiant problem inferred from direct progenitor detections, discussed in section 4 (although see Anderson et al 2018 for a reportedly high-mass progenitor case in a low-metallicity environment). Studies of the SN light curve evolution, that primarily constrain the ejecta masses of the event, are in general agreement with the above studies (e.g., Valenti et al 2016;Martinez & Bersten 2019;Eldridge et al 2019).…”
Section: Predicted Discrepancy Of Inferred Initial Masses Of Type II Sn Progenitors Between Different Observational Methodssupporting
confidence: 85%
“…This is consistent with the red supergiant problem inferred from direct progenitor detections, discussed in section 4 (although see Anderson et al 2018 for a reportedly high-mass progenitor case in a low-metallicity environment). Studies of the SN light curve evolution, that primarily constrain the ejecta masses of the event, are in general agreement with the above studies (e.g., Valenti et al 2016;Martinez & Bersten 2019;Eldridge et al 2019).…”
Section: Predicted Discrepancy Of Inferred Initial Masses Of Type II Sn Progenitors Between Different Observational Methodssupporting
confidence: 85%
“…Smartt et al 2009; and hydrodynamical models (e.g. Bersten, Benvenuto & Hamuy 2011;Dessart et al 2013b;Martinez & Bersten 2019). Although there remain some disagreements (e.g.…”
Section: Progenitor Massmentioning
confidence: 99%
“…Smartt et al 2009; and hydrodynamical models (e.g. Dessart et al 2013b;Martinez & Bersten 2019). However, other studies have suggested the possibility that their progenitors are more massive RSGs with large amounts of fallback material (e.g.…”
mentioning
confidence: 99%
“…MESA+STELLA progenitor and light-curve modeling. Recent work 72,98,99,100 highlights the nonuniqueness of bolometric light-curve modeling for extracting explosion characteristics (ejecta mass M ej , explosion energy E exp , and progenitor radius R) from plateau features (in particular, luminosity at day 50, L 50 , and plateau duration, t p ) without an independent prior on one of M ej , E exp , or R. Due to the presumed presence of a dense CSM and its potential influence on the early light curves and velocities, shock-cooling modeling and early expansion velocities cannot simply lift this degeneracy.…”
mentioning
confidence: 99%